Ranking Based Security Scheme with Attack Detection and Improved Network Security - Walde, Rajesh B.; Prakash, Om; Kumar, M. Sunil; Sule, Bipin; Nabilal, Khan Vajid; Pawar, Usha C. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
: In the diverse environment anomaly detection significant challenge for the efficient analysis of the data traffic monitoring, medical domain, transaction of financial data, web log, domain for transportation, wireless mobile network and so on. Wireless network comprises of the different factors such as ease of use and reduced running cost in the network. MANET network comprises of the infrastructure less, auto configured, dynamic topology and central administration in the network node. This paper concentrated on the examination of the challenges in the MANET attack security challenges and proposed an anomaly detection scheme. The proposed anomaly detection scheme incorporates the scoring procedure for the anomaly detection in the network. The anomaly detection score computes the ranking values in the MANET network for the analysis. The developed ranking-based anomaly detection scheme is defined as the Ranking Anomaly Score (RAS). The performance of the RAS model is evaluated in terms of throughput, Packet delivery rate (PDR) and end -to-end delay. The performance of the proposed RAS model is comparatively examined with the existing Hashing, AODV and RSA. The comparative analysis expressed that proposed RAS model achieves the maximum throughput of 1600 bits/sec, maxima PDR is 98% and end-to-end delay is measured as 14ms. Through analysis it is observed that proposed RAS model achieves improved performance compared with the conventional technique.